The case of the recent South African mineworkers strike : analysing and evaluating Broad-Based Black Economic Empowerment. - Githu, Charlene Wanjiku (My University, 2016)
Broad-Based Black Economic Empowerment is analysed in the context of the South African mining industry. The areas of investigation include trials and tribulations associated with implementing Broad-Based Black Economic Empowerment through the mining charter within the platinum sector of the mining industry, the contribution of the mining industry towards to the South African Gross Domestic Product and the causes associated with the recent strikes taking place between 2007 and 2014 within the platinum sector of the mining industry. The findings of this research suggest that Broad-Based Black Economic Empowerment is essential for South Africa as it is concerned with empowering those that were repressed to participate meaningfully within the South African economy in order to achieve economic transformation. B-BBEE through the mining charter is still considered to be associated with equity ownership and as a result, narrow based Black Economic Empowerment is implemented. The implementation of the narrow based approach is concluded to be the result of the priority elements of implementation, South Africa’s unfavourable economic climate and a lack of a general understanding with regards to empowerment, transformation and B-BBEE. The findings of this research indicate that the narrow based implementation of B-BBEE through the mining charter caused a catalytic reaction towards to the strikes that occurred within the platinum sector of the mining industry between 2007 to 2014 as the causes of the strikes are suggestive of the lack of social opportunities. The research report concludes with changes required for further transformation to take place, which requires more than changes to existing socio-economic policies alone.
MBA
Keywords: Blacks -- Employment -- South Africa. Employee empowerment -- South Africa. Platinum industry -- South Africa -- Management. Mineral industries -- South Africa -- Management.